The Parents’ Knowledge Level and the Pattern of Vitamin A and Daily Food in Early Childhood - L D, Zulfikar; Farfar, Inggrid Osya; Desi Hartati (Universitas Kristen Krida Wacana, 2025)
Vitamin A deficiency remains a public health issue, particularly among early childhood populations. Night blindness is one of the early consequences of vitamin A deficiency, which can be prevented through adequate nutritional intake. Parents play a crucial role in shaping their children’s eating habits from an early age. Objective of research is to determine the relationship between parents’ knowledge level and the pattern of vitamin A and daily food intake in the prevention of night blindness in early childhood in Sawah Baru Subdistrict. This study used a quantitative approach with a cross-sectional design. Data were collected through questionnaires and structured interviews with 111 respondents who were parents of children aged 3 to 7 years. Data were analyzed using the Chi-Square test. The majority of respondents had a moderate level of knowledge (57.7%), and their children's patterns of vitamin A and daily food intake were also in the moderate category. Statistical tests showed no significant relationship between parents' knowledge level and vitamin A intake patterns (p=0.133) or daily food intake (p=0.848). Parents' knowledge alone is not sufficient to ensure optimal feeding behavior in the prevention of night blindness. Other factors such as family economy and dietary habits also play a role.